English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I know this is the chain rule, but I'm rather rusty on my calculus techniques at the moment and am struggling:

y=x10^[ (344/825)x+(43/12) ] - c

where c is any real number.

Thank you.

2006-12-30 06:45:16 · 7 answers · asked by Tom 1 in Science & Mathematics Mathematics

7 answers

y = x10^[ (344/825)x+(43/12) ] - c

Move c to the LHS and take ln,
ln( y+c) = ln x + [ (344/825)x+(43/12) ] (ln 10)

Differentiate both sides,
y'/(y+c) = 1/x + (344/825)( ln 10)

Substitute y+c and move it to the RHS,
y' = x10^[ (344/825)x+(43/12) ][1/x + (344/825)(ln 10)]

Simplify,
y' = 10^[ (344/825)x+(43/12) ][1 + (344x/825)( ln 10)]

---------------------------

You can also use exponential function y = e^(lny) to start, which is little bit simpler.

2006-12-30 07:07:43 · answer #1 · answered by sahsjing 7 · 0 0

y=x10^[ (344/825)x+(43/12) ] - c

Let a = 344/825 and b = 43/12, then
y = x * 10^(ax + b) - c

Use the product rule : d(uv)/dx = u * dv/dx + v * du/dx

Therefore, y' = x * d[10^(ax + b)]/dx + 1 * 10^(ax + b) + 0
noting that the derivative of the constant c is 0.

For d[10^(ax + b)]/dx, use the formula :
d(a^u)/dx = a^u * ln(a) * du/dx

Thus, y' = x * [10^(ax + b) * ln(10) * a] + 10^(ax + b)

Finally, y' = 10^(ax + b) * [ax * ln(10) + 1]

Substituting back for a and b gives :

y' = 10^[(344/825)x + 43/12] * [(344/825) * ln(10) * x + 1]

2006-12-30 15:25:13 · answer #2 · answered by falzoon 7 · 0 0

Given:y=x10^[(344/825)x+(43/12)]-c

step1:assign x as 'u' and 10^.... as 'v'.. ..and 344/34 as "a" and 43/12 as b to simplify matters......and forget about c as it gets canceled off under differentiation(real no. is a constant)
so y= x10^(ax+b)
2:dy/dx of uv= udv+vdu
This implies dy/dx= x.[dy/dx(10^(ax+b)]+10^(ax+b).dy/dx[x]....(1)

Now don't you feel the sum is easier???

Now you solve it by applying the BASIC formulas..
dy/dx[x]=1.....(2)
dy/dx(10^(ax+b)= [ax+b]10^[(ax+b)^-1].a........(3)

substitute the results of (2) and (3) in (1) and also the values of "a" and "b"... you will get the final answer...

2006-12-30 15:07:26 · answer #3 · answered by Hari 2 · 0 0

Well, first off, c is useless. It gets cancelled out, so just cross it off the page. If you put this in correctly, it is more than just the chain rule. You need to use the product rule {(uv)'=v'u+u'v}, x being u and 10^... being v. Then, when you differentiate 10^... you need to use the chain rule. Any number to a power differentiated uses the rule (a^u)'=(a^u)(ln a)(du/dx). You should be able to do it on your own given those formulas.

If you can't figure it out on your own, and no one answers it, email me and I'll send you the answer.

2006-12-30 14:53:39 · answer #4 · answered by northwestsk8 1 · 0 0

Phew - I thought I passed maths A level. But it was 40+ year ago

2006-12-30 14:55:33 · answer #5 · answered by Davy B 6 · 0 0

I just finished an exam in this and i'm still clueless!

2006-12-30 14:54:34 · answer #6 · answered by Anonymous · 0 0

hahaha i wish i could help but im in algebra 1 AGAIN lol

2006-12-30 14:49:17 · answer #7 · answered by Harlequin. 2 · 0 1

fedest.com, questions and answers